2013
DOI: 10.1016/j.curtheres.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Platelet-Rich Fibrin in Combination With Biphasic Calcium Phosphate in the Treatment of Bone Defects: A Histologic and Histomorphometric Study

Abstract: BackgroundPlatelet-rich fibrin (PRF) is a leukocyte and platelet concentrate containing many growth factors. Its potential for hard tissue augmentation as a sole grafting material or in combination with other grafting materials has been investigated in many studies.ObjectiveThe aim of this histologic study was to evaluate the efficacy of PRF mixed with biphasic calcium phosphate (BCP) on bone regeneration in surgically created bone defects.MethodsDefects 5 mm in diameter were created in both tibias of 6 sheep.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 32 publications
(12 reference statements)
1
28
0
Order By: Relevance
“…30,31 In this study, we fabricated an innovative 3D printed porous nano-BCP/PVA/PRF scaffold. There is little research on the combination of these three materials for bone repair applications, [32][33][34] let alone the 3D printing of this mixture. We hypothesized that the low-temperature 3D printing of BCP/ PVA/PRF scaffolds would preserve the biological activity of PRF and provide an innovative biomaterial for restoring segmental bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 In this study, we fabricated an innovative 3D printed porous nano-BCP/PVA/PRF scaffold. There is little research on the combination of these three materials for bone repair applications, [32][33][34] let alone the 3D printing of this mixture. We hypothesized that the low-temperature 3D printing of BCP/ PVA/PRF scaffolds would preserve the biological activity of PRF and provide an innovative biomaterial for restoring segmental bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing interest in understanding the effects of platelet concentrate application on bone tissue is reflected in the number of recent studies that have examined this topic (Al‐Hamed et al, ; Canellas et al, ; Cortese et al, ; Isobe et al, ; Panda et al, ). Although there have been studies that have used models of bone lesions in animals to clarify the effects of these platelet concentrates at different levels (Acar et al, ; Bölükbaşı, Yeniyolm, Tekkesinm, & Altunatmaz, ; Du et al, ; Ocak et al, ), there are also clinical studies that focus on radiological (Cortese et al, ; Park et al, ) and tomographic analyses (Lim et al, ; Montanari, Callea, Yavuz, & Maglione, ; Öncü & Kaymaz, ) and its use in clinical settings (Barone et al, ; Panda et al, ; Sezgin, Uraz, Taner, & Çulhaoğlu, ), all of which seek to evaluate the effects of this therapy. Our clinical case study differs from these investigations as it evaluates the ultrastructure of neoformed bone tissue and the quantity of inorganic elements of HA present.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of morphological and morphometric studies at the histological level have yielded inconclusive evidence of the overall effect of PRF use. Some of these studies revealed positive effects resulting from PRF application, such as improvements and increased bone formation in sheep (Bölükbaşı et al, ) and porcine (Yilmaz et al, ) tibia.…”
Section: Discussionmentioning
confidence: 99%
“…PRF was cut and mixed with β-TCP particles to be applied inside the created defects then covered by PRF membrane; collagen membrane was placed to completely cover the augmented defect. This technique of PRF application was also carried out by Bölükbaşı et al; (10) to maximize the contact between the defect walls and PRF from inside and from outside in order to maximize the effect of PRF. Although Bölükbaşı et al; (10) did not cover their created defects with collagen membranes we utilized collagen membranes in both groups to standardize the study approach, so any histological changes observed in either group will be attributed mainly to the role of the applied material only.…”
Section: Dicussionmentioning
confidence: 99%